An MASW survey for landslide risk assessment in novi seher, Bosnia and Herzegovina- A case history - Suto, K.; Urosevic, Milovan; Komatina, S. (2017)
A heavy rainfall caused an extensive damage in the catchment area of River Sava in May 2014. In response, the Association of Geoscientists and Environmentalists of Serbia organized a Geoscientists without Borders project for 2015-2016 to assess landslide potential at six locations of Serbia and Bosnia and Herzegovina. Geophysicists from many parts of the world, local students, local government staff and local residents participated in the surveys carried out in three phases. Among these surveys, this paper presents one in Novi Seher in Bosnia and Herzegovina. The data were primarily collected for reflection survey and the MASW processing used a subset of the data by extracting appropriate traces. The analysis resulted in S-wave velocity sections which are geologically plausible, with a potential slip surface between 0 and 10m deep. This result will be integrated with seismic reflection and refraction analyses to contribute to designing disaster mitigation plan.